Corpos (im)possíveis: o sujeitoLGBTQIAPN+ na trama do discurso publicitário em comerciais da Avon, Natura e TheBody Shop - Oliveira, Kassia Paloma Beltrame (2023)
This research delves into the constitution of the LGBTQIAPN+ subject's body within the realm of discourse, specifically exploring how it is shaped by the ideological underpinnings of Brazilian advertising discourse. Our focus centers on the diverse significant materialities that (inter)compose the analyzed advertising films, namely bodies/images, gestures, musicality, and expressions, each contributing to meaning effects and the construction of the subject. The corpus comprises two advertising films: "A primeira vez" (2017), developed by Natura, and "Mais do que você vê" (2020), a collaboration between Natura, Avon, and The Body Shop, all presented in June during the "LGBTQIAPN+ Pride Month." The research is guided by the following questions: How are LGBTQIAPN+ subjects represented through the interweaving of significant materialities in the chosen films? What subjects emerge, and what memories define them, shaping the entirety of advertising discourse? What meanings surface from the pervasive silencing within the discourse? What are the implications of societal influence on the LGBTQIAPN+ subject, and how is it (re)constructed through advertising discourse?For this dissertation, we employ French Discourse Analysis (DA) as proposed by Michel Pêcheux. This discipline provides the theoretical and methodological framework for analyzing the constitution of these subjects' bodies and the potential meaning effects in the selected advertising films. Through the intertwining of distinct significant materialities, we identify discursive imprints of a resistance-image body (emanating from the social), a memory-body, an (im)possible-body, and a non-transparent apagamento-body, each interacting and constituting various LGBTQIAPN+ bodies. The results indicate that the films depict memories integral to the constitution of LGBTQIAPN+ subjects, encompassing experiences of discrimination, exclusion, and marginalization, as well as the movements' struggles and achievements for rights, visibility, and representation. Despite advertising serving as a communication strategy aimed at commercial objectives, where campaigns seek to retain consumers identifying with the diversity represented by the brands, we observe that the commercial interest in promoting diversity does not diminish the significance of the discourse conveyed in these campaign